Gambaran Escherichia coli resistan antibiotik asal tangan pemerah, ambing sapi, susu serta air di Peternakan Sapi Perah Kecamatan Cendana, Enrekang, Sulawesi Selatan - Milawarni Milawarni; Herwin Pisestyani; Denny Widaya Lukman (Livestock and Animal Research, 2022)
Objective: This study aimed to describe the resistance of E. coli to several types of antibiotics isolated from water, milker hand swabs, cow udder swabs and milk in the Enrekang dairy farm, South Sulawesi.Methods: Isolation and identification of E. coli refers to SNI 2897:2008 concerning Methods for Testing Microbial Contamination in Meat, Eggs and Milk, and their Processed Products. The test of E. coli resistance to antibiotics by disc diffusion method and interpretation of the results refers to the Clinical and Laboratory Standards Institute (CLSI). The samples were 13 milker hand swabs, 52 cow udder swabs, 52 individual milks, and 13 water used for rearing activities.Results: E. coli isolates (n=64) consisted of 7 isolates from hand swabs, 7 isolates from milking hands, 20 isolates from udder swabs, 31 isolates from milk, and 6 isolates from water. E. coli isolates were resistant to erythromycin and ampicillin as much as 78%, trimethoprim-sulfamethoxazole 34.4%, tetracycline 31%, ceftazidime 25%, chloremphenicol 22%, enrofloxacin 9.4%, and gentamicin 4.6%. The pattern of E. coli resistance to antibiotics showed that the isolates of E. coli multiple drugs were resistant to up to 7 antibiotics at once.Conclusions: E. coli isolates from milk, cows, milk and water in the Enrekang dairy farming area, South Sulawesi has developed resistance to several types of antibiotics and have the potential to spread resistance genes to other bacteria and threaten human, animal and environmental health.